2020
DOI: 10.4317/jced.57125
|View full text |Cite
|
Sign up to set email alerts
|

Two rare cases of oral metastasis arising from lung adenocarcinoma and esophageal carcinoma

Abstract: Metastasis to the oral cavity are rare, representing only 1% of all oral malignancies, and originate from various sites such as the breast, prostate, lung and kidney. Clinically, they can simulate reactive and inflammatory lesions common in the oral cavity, and the clinical and microscopic diagnosis of these metastasis is a challenge. In this article, we report two new cases of esophageal and lung metastasis to oral tissues, highlighting their clinical characteristics and the process of diagnostic elucidation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…3 Recent literature has shown metastases to unusual sites. [4][5][6][7] Shaheen et al 10 found the most common unexpected metastatic site group was the head and neck, and of specific organs, skin was most common. Within abdominopelvic, the kidneys, pancreas, and spleen were most common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Recent literature has shown metastases to unusual sites. [4][5][6][7] Shaheen et al 10 found the most common unexpected metastatic site group was the head and neck, and of specific organs, skin was most common. Within abdominopelvic, the kidneys, pancreas, and spleen were most common.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Reports indicating uncommon metastatic sites include maxillary bone, 4 skeletal muscle, 5 subcutaneous tissue, 6 and the oral cavity. 7 However, scant literature has been published regarding metastasis to the female reproductive tract, with only 2 published cases demonstrating esophageal metastasis to the ovaries. 8 , 9 Early detection may prevent unproductive treatment and improve prognosis.…”
Section: Introductionmentioning
confidence: 99%